2016
DOI: 10.1016/j.pec.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving one’s heart condition to be cured following hospitalization for acute coronary syndromes: Implications for patient-provider communication

Abstract: Objective We examined the proportion of patients perceiving their heart condition to be cured following hospitalization for ACS and identified characteristics associated with these perceptions. Methods We conducted a prospective cohort study of adults hospitalized with ACS (N=396). Patient interviews during hospitalization and one week post-discharge provided demographic and psychosocial characteristics. Medical records provided clinical characteristics. At one week, patients who rated “My heart condition is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The medically managed patient would score above the screening cutoff for PTSD diagnosis (i.e., ≥33; see the portion of Figure 1 to the right of the vertical gray line), whereas the revascularized patient would score 14 points lower (corresponding to ~ 1 SD on the PCL-S), suggesting little impact of the ACS on psychological well-being (National Center for PTSD, 2014). This difference is large but consistent with the EST model of ACS-induced PTSD, which suggests that no matter how acutely threatening the index ACS event, patients who believe that the cause of the ACS has been “cured” (Rothberg et al, 2010; Waring et al, 2016) may have lower risk for subsequent PTSD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The medically managed patient would score above the screening cutoff for PTSD diagnosis (i.e., ≥33; see the portion of Figure 1 to the right of the vertical gray line), whereas the revascularized patient would score 14 points lower (corresponding to ~ 1 SD on the PCL-S), suggesting little impact of the ACS on psychological well-being (National Center for PTSD, 2014). This difference is large but consistent with the EST model of ACS-induced PTSD, which suggests that no matter how acutely threatening the index ACS event, patients who believe that the cause of the ACS has been “cured” (Rothberg et al, 2010; Waring et al, 2016) may have lower risk for subsequent PTSD.…”
Section: Discussionsupporting
confidence: 63%
“…Because the EST model posits that perception of ongoing threat in the body is the central driver of PTSD symptoms in ACS patients, we hypothesized that receiving a revascularization procedure would be associated with decreased ACS-induced PTSD symptoms at 1 month relative to receiving medical management only. Previous research has shown that ACS patients who undergo cardiac catheterization with revascularization are 4 times more likely to believe they are “cured” than patients who are medically managed (Roth-berg et al, 2010; Waring et al, 2016). Similarly, for some types of ischemic heart disease, recent sham-controlled trials suggest that patient-reported benefits of stents from prior randomized controlled trials were likely due to powerful placebo effects of invasive procedures (Al-Lamee et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%
“…From September 2011 to May 2013, consecutive TRACE-CORE participants from the Worcester sites were invited to enroll in TRACE-CARE, an ancillary study to TRACE-CORE designed to further examine psychosocial factors and caregiver support during the early post-discharge period. Details of the ancillary TRACE-CARE study have been previously described (Waring et al, 2015). Consenting participants ( n = 585, 96% of invited participants) were contacted at home via telephone 1 week (range = 5-10 days) after hospital discharge.…”
Section: Methodsmentioning
confidence: 99%